Portraying monsters: framing school bullying through a macro lens. Issue 2 (3rd March 2016) - Horton, Paul
Abstract : This article critically considers the discourse on school bullying through the conceptual framework of lenses and argues that a macro lens has been utilised by school bullying researchers to bring into focus the characteristics of the individuals involved and the types of actions used. By considering earlier understandings of bullying, the article illustrates how this macro lens has become a metalens through which school bullying is understood. This has had implications for how bullying is understood and addressed, as well as for how vast numbers of school-aged children are perceived and treated. The article argues that the macro lens needs to be replaced with a wide-angle lens, so as to bring the social, institutional and societal contexts into view.